ALOE VERA MENDONGKRAK KEHIDUPAN KELOMPOK NON PRODUKTIF EKONOMI - Erna Haryanti; Endang Noerhartati; Indarwati Indarwati; Dwie Retna. S; M. Aziz (Indonesian Collaboration Journal of Community Services, 2021)
The existence of local potential  of Aloe Vera plants that grow wildly, and another side is need to foster an entrepreneurial spirit in housewives who do not earn economically, is  impetus to carry out Community Service through the Cultivation and Processing of Aloe Vera Products to be developed into prospective entrepreneurial objects. Community Service is carried out in RW IX, Dukuh Kupang Timur, RT 03 and RT 05. This activity includes targets starting from the preparation of activity, organizing, implementing as well as monitoring and evaluation. This method has a positive impact, namely the growth of a larger sense of belonging from the target and support from related agencies. So that community service activities can be easily carried out. This community service is carried out by transfers science and technology of  cultivation, product processing, business aspects and entrepreneurial motivation. Added value of aloe vera cultivation are carried out by processing aloe vera Becomes Sticks, Kremes Noodles, Coktails, drink with coconut milk and brown sugar , Pudding, Crackers, and Aloe Vera tea. From this activity emerged entrepreneurs of aloe vera and its processed products,  which through periodic and intensive assistance are expected to become sustainable entrepreneurial activities